(untitled) (Patan Pragya, 2023)
This article examines Sita Pandey’s Fever, an anthology of stories about pain, suffering, and stereotypical depictions of women. The story deals with the oppression of women in patriarchy. Women do housework, serve their husbands, and work long hours and after-hours. They become alienated, frustrated, and mentally and physically broken. The cause of their suffering is none other than patriarchy. Patriarchy imposes laws on women that affect their identity and existence. Society gives them difficult roles and limits their roles. Women live according to patriarchal norms and values, suppressing their own desires. Female characters are depicted as mere servants guided by their emotions. Society is a great example of the ignorance and blind exploitation of women. Society requires women to have passion in their eyes, lust for women’s bodies, and admire the beauty of women’s bodies. Just as Prema is compared to wine in the story ’Own Question Mark’, men compare women to inanimate objects. Female characters are seen by men simply as objects of beauty, pleasure, and satisfaction. The stories contained in Fever visualize the memories of women’s oppression, alienation, and depression in society. This article creates an overview of the pain, grief, suffering, hardship, and haunting memories of female characters, exploring their lost identity, respect, and dignity.